Market Reaction to Earnings Announcements of Successful Efforts and Full Cost Firms in the Oil and Gas Industry - Bandyopadhyay, Sati P. (The Accounting Review, 1994)
[From time to time over the last 25 years, the Accounting Principles Board (APB), the Financial Accounting Standards Board (FASB) and the Securities and Exchange Commission (SEC) have debated whether successful efforts (SE) or full cost (FC) accounting provides investors (creditors) with the more informative accounting numbers and thus should be mandated for all oil and gas firms.1 (See Deakin 1989 and Collins, Rozeff and Salatka 1982, for a description of regulatory events surrounding the SE versus FC controversy.) This debate is related to the notion of "quality of earnings" which has received some attention both in the popular press (Donelly 1990; O'Glove 1987) and in the academic accounting literature (Collins and Salatka 1993 on foreign currency accounting; Pincus and Wasley 1992 on Lifo/Fifo; and Carroll, Collins and Johnson 1993 on Lifo/Fifo). Results from the academic literature suggest that certain accounting procedures appear capable of producing superior quality earnings numbers which are highly valued (priced) by the market, while some other accounting procedures are not. The current study provides further insight into the potential effects of accounting policy choice on earnings quality by examining whether SE and FC earnings are priced differently by the market. Despite the regulatory interest in the quality of SE versus FC accounting, there is relatively little evidence on whether investors evaluate SE and FC accounting numbers differently. Harris and Ohlson (1987) found that SE firms exhibit higher market-to-book coefficients than FC firms, a result consistent with Sunder's (1976) finding that the SE method produces more conservative net assets and income numbers than the FC method. Ayres and Rayburn (1991) regress annual security returns on annual earnings changes and supplemental reserve information variables for SE and FC firms and find that SE firms have higher coefficients on the earnings change variable than FC firms. This study provides evidence on the quality issue by comparing the earnings response coefficients (ERCs) of SE and FC firms surrounding their quarterly earnings announcement dates over the 1982-1990 period. Short event windows are selected for analysis to accentuate SE versus FC effects: timing differences between accounting numbers related to different methods of cost recognition (such as SE and FC) tend to decline over longer horizons. Predictions are based on Ramakrishnan and Thomas' (1992) argument that the FC method imparts considerable price-irrelevant elements to earnings by capitalizing and amortizing exploration costs associated with dry holes (which have no future cash flow generating ability). SE accounting's immediate recognition of dry hole costs occurs in the same period in which the market would react to the information about the unproductive exploration activity. This is consistent with SE earnings being viewed as better quality earnings than FC earnings. According to this view of earnings quality, a high quality earnings number is generated when valuation relevant events are recognized in the same fiscal period in which they are recognized in returns (see, for example, Lev 1989). This notion of earning quality also implies that SE ERCs are likely to be larger than FC ERCs. The main finding of the study is that SE ERCs are, on average, greater than FC ERCs over the entire sample period. Unlike some prior studies, empirical tests in this paper control for the potentially confounding effects of exploration activity, growth, risk, earnings predictability and earnings persistence on ERCs. Ayres and Rayburn (1991), who found long-window SE ERCs to be larger than FC ERCs, control for potential risk and size effects but not for other factors; Spear (1993) also does not examine the effects of potentially confounding factors in his research design.2 However, the main finding is sensitive to time-partitions. SE ERCs, on average, exceed FC ERCs during 1982-1985 but not during 1986-1990. The latter period is one of relative decline in the level of exploration activity due to a dramatic oil price decline in 1986. The consequent drop in exploration activity led to the examination of time partitions because differences across SE and FC numbers are accentuated when the level of exploration activity is high. It is interesting to observe that FC firms have smaller ERCs despite having, on average, the same persistence in their reported earnings as SE firms. This apparent puzzle is again explained in the analysis of Ramakrishnan and Thomas (1992). FC firms achieve persistence in their reported earnings series by deferral and amortization of dry hole costs which are price-irrelevant in periods subsequent to the outlay. In effect, one observes the persistence of accounting accruals rather than persistence that reflects cash flows. The ERC results support the notion that the market attaches no value to persistence created by accounting accruals. In the context of Ramakrishnan and Thomas' (1992) analysis, ERCs increase in persistence only when that persistence reflects underlying economic characteristics (i.e., cash flow effects).]